DYNAMICS ANALYSIS OF MEDICAL-DEMOGRAPHIC PARAMETERS IN THE KYRGYZ REPUBLIC - R. M. Atambaeva; G. S. Kitarova; E. Y. Kondratyeva (Педиатрическая фармакология)
The article presents results of demographic status assessment of the Kyrgyz Republic, discusses trends of the main medicaldemographic parameters characterizing the nation and shows that the socioeconomic changes that have been taking place in the recent decades continue having considerably effect on population health formation and change of demographic processes.